2020
DOI: 10.1177/2382120520965254
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Curriculum for Medical Student Training in LGBTQ Healthcare: A Regional Pathway Experience

Abstract: Background: Lesbian, gay, bisexual, transgender, and queer (LGBTQ) individuals face considerable health disparities, often due to a lack of LGBTQ-competent care. Such disparities and lack of access to informed care are even more staggering in rural settings. As the state medical school for the Washington, Wyoming, Alaska, Montana, and Idaho (WWAMI) region, the University of Washington School of Medicine (UWSOM) is in a unique position to train future physicians to provide healthcare that meets the needs of LGB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 10 publications
0
21
0
11
Order By: Relevance
“…Additionally, allied healthcare professional education could take a regional approach and seek to foster competent and affirming care in rural settings [ 83 ]. For example, in their LGBTQ curriculum pathway, the University of Washington School of Medicine required students to engage in advocacy/community activities with rural LGBTQ+ organizations [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, allied healthcare professional education could take a regional approach and seek to foster competent and affirming care in rural settings [ 83 ]. For example, in their LGBTQ curriculum pathway, the University of Washington School of Medicine required students to engage in advocacy/community activities with rural LGBTQ+ organizations [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, allied healthcare professional education could take a regional approach and seek to foster competent and affirming care in rural settings [ 83 ]. For example, in their LGBTQ curriculum pathway, the University of Washington School of Medicine required students to engage in advocacy/community activities with rural LGBTQ+ organizations [ 83 ]. Indeed, while TEACHH took place in urban settings, rural care of trans women and trans women living with/affected by HIV is of critical importance, given studies showing perceived inadequacies in rural provider competency to provide affirming care and subsequent challenges faced by rural LGBTQ people, including higher rates of discrimination, lower likelihood of sexual/gender minority identity disclosure, and health disparities [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are no diversity-oriented medical trainings that focus specifically on ED interventions or training. Some contemporary examples of diversity-oriented medical trainings have been evaluated at mostly North-American universities and institutions, although there are only a few examples of extensive curricula (99,100). Furthermore, diversity trainings of the kind are often offered separately from general education, usually geared toward specific minority groups, and offered voluntarily, thus bearing the risk that only a limited number of students (e.g., those with prior knowledge and interest in the subject, and the willingness to question their positions) will participate.…”
Section: Diversity In Ed-related Clinical Educationmentioning
confidence: 99%
“…One study reported that the LGBTQ Health Pathway program developed by a student-driven curriculum enables medical students to enhance their training in the care of LGBT+ patients. It also reported that the LGBTQ program enhanced medial students' interest in LGBT+-related medicine [28]. One study reported that increasing the amount of LGBT+ teaching in undergraduate medical curricula could increase medical students' awareness of LGBT health issues and increase positive attitudes towards LGBT+ patients [29].…”
Section: Lgbt+ Health Care and Gender Educationmentioning
confidence: 99%